1991
DOI: 10.1128/jb.173.16.5030-5035.1991
|View full text |Cite
|
Sign up to set email alerts
|

Cofactor requirements of BamHI mutant endonuclease E77K and its suppressor mutants

Abstract: A mutant BamHI endonuclease, E77K, belongs to a class of catalytic mutants that bind DNA efficiently but cleave DNA at a rate more than 103-fold lower than that of the wild-type enzyme (S. Y. Xu and I. Schildkraut, J. Biol. Chem. 266:4425-4429, 1991). The preferred cofactor for the wild-type BamHI is Mg2+. BamHI is 10-fold less active with Mn2+ as the cofactor. In contrast, the E77K variant displays an increased activity when Mn2+ is substituted for Mg2, in the reaction buffer. Mutations that partially suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…A recent report indicates that EcoRV can bind to DNA in the absence of Ca 2ϩ or Mg 2ϩ under different conditions (44); attempts to visualize a gel shift for PvuII in the absence of metal ions or in the presence of Mg 2ϩ for the catalytically inactive mutants have thus far been unsuccessful. Similar mutagenesis studies have been done on EcoRI (10 -13, 15, 45), EcoRV (18,20,23,24,28), and BamHI (26,27,30). These studies have anticipated or confirmed the predicted roles of residues identified as central from the crystal structures of the respective enzymes.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A recent report indicates that EcoRV can bind to DNA in the absence of Ca 2ϩ or Mg 2ϩ under different conditions (44); attempts to visualize a gel shift for PvuII in the absence of metal ions or in the presence of Mg 2ϩ for the catalytically inactive mutants have thus far been unsuccessful. Similar mutagenesis studies have been done on EcoRI (10 -13, 15, 45), EcoRV (18,20,23,24,28), and BamHI (26,27,30). These studies have anticipated or confirmed the predicted roles of residues identified as central from the crystal structures of the respective enzymes.…”
Section: Discussionmentioning
confidence: 88%
“…Structure-function studies have been limited to a small number of type II enzymes. Years of studies have produced an extensive amount of information about EcoRI (10 -18), EcoRV (18 -24), and NaeI (25) and, more recently, BamHI (26,27). These studies have focused on the identification and analysis of residues involved in catalysis, testing alternative mechanisms of catalysis, and understanding how a specific DNA sequence is recognized.…”
mentioning
confidence: 99%
“…146 The activity of Glu-77/Lys mutants is enhanced in the presence of suppressor mutations that may optimize the positioning of the mutant cationic side chain. 147 Thus, in both studies 144,145 the term "two-metal ion mechanism" is used even though EcoRV contains only one metal ion (although replacement of the ammonium side chain of Lys-92 by Glu-92/Mn 2+ restores activity), 144 while BamH1 contains two metal ions 145 (one of which may be replaced by the ammonium side chain of Lys). 146,147 These results indicate that metal ions and positively charged amino acid side chains can be interchangeable for classes of enzyme that share a common mechanism.…”
Section: Electrostatic Induction By Divalent Metal Ionsmentioning
confidence: 99%
“…In principle, it is possible that the BamHI enzyme creates a double-strand break to mediate integration events or that it binds to BamHI recognition sites to bring the recombination partners together. Furthermore, since restriction enzymes show nonspecific weak DNA binding (46), restriction enzymes could possibly bind to the transforming DNA and enhance uptake of such DNA indirectly, leading to an increase …”
Section: Resultsmentioning
confidence: 99%
“…To address this possibility, we used purified BamHI-E77K protein, which binds to the BamHI site but cleaves DNA at a rate 1,000-fold lower than that of wild-type enzyme (46). The BamHI-E77K protein did not increase the efficiency of integration ( Table 1), indicating that the cutting activity of the restriction enzyme is necessary to mediate REMI events.…”
Section: Resultsmentioning
confidence: 99%